2020
DOI: 10.1016/j.tcb.2020.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Cell Plasticity in Liver Regeneration

Abstract: The liver, whose major functional cell type is the hepatocyte, is a peculiar organ with remarkable regenerative capacity. The widely held notion that hepatic progenitor cells contribute to injury-induced liver regeneration has long been debated. However, multiple lines of evidence suggest that the plasticity of differentiated cells is a major mechanism for the cell source in injury-induced liver regeneration. Investigating cell plasticity could potentially expand our understanding of liver physiology and facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 79 publications
1
86
0
3
Order By: Relevance
“…HBs proliferate vigorously and remain bipotent at the liver bud stage during embryogenesis, which is influenced by signals from the surrounding mesenchyme. Similarly, expansion and maintenance of HBs identity in vitro are highly dependent on precise regulation by extrinsic and intrinsic signals [21]. Previous studies have demonstrated that stimulation of Wnt and inhibition of TGF-β were both important for hepatic proliferation [7,14,22].…”
Section: Discussionmentioning
confidence: 99%
“…HBs proliferate vigorously and remain bipotent at the liver bud stage during embryogenesis, which is influenced by signals from the surrounding mesenchyme. Similarly, expansion and maintenance of HBs identity in vitro are highly dependent on precise regulation by extrinsic and intrinsic signals [21]. Previous studies have demonstrated that stimulation of Wnt and inhibition of TGF-β were both important for hepatic proliferation [7,14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Cell plasticity is also implicated in non-nutritional physiological responses. During chronic periportal liver injury, hepatocytes de-differentiate into liver progenitor-like cells simultaneously expressing markers for hepatocytes and biliary epithelial cells and regenerate hepatocytes and duct-like cells [ 78 ]. These examples suggest that alterations in cellular identity may play an important role in physiological and pathological responses implicated in a broad range of human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…HPCs are responsible for developing CPCs and cholangiocytes [26]. Hepatocytes exhibit plasticity to recruit bile ductular cells under liver physiological and pathological conditions [34]. Transplanted hepatocytes can differentiate into bile ductular cells in bile duct ligation model animals [35].…”
Section: Discussionmentioning
confidence: 99%